OPTIMASI DESAIN SISTEM HIDRAN GEDUNG X DENGAN KETINGGIAN 140 METER - Larasati Suciningsih (2021)
Hydrant system is one of the fire fighting installation that functions to distribute pressurized water to extinguish fire. As a building utility, hydrant system must be properly designed because it involves safety of the building and the life in it. Building X has a hydrant system divide into two zone, low zone and high zone, each zone have friction losses of 8.08 and 8.06 meter calculated with hazen-williams equation. Design optimization is carried out with the purpose to reduce friction loss by diverting the top three floors of low zone (12,13,14) to high zone and increase diameter of the pipe from 6 in to 8 in. Design optimazization results show that friction losses of low zone and high zone decerase into 3.53 meter and 3.7 meter. The decerase of friction loss gives impact to the decerase of fire pump head from 140 meter (low zone) to 125 meter and 145 meter (high zone) to 140 meter, it also gives impact to power of the pumps decerase from 122 Kw (low zone) to 109 kW and 95 Kw (high zone) to 85 kW. Design optimization successfully reduce the friction loss of hydrant system, each zone decerases up to 56.3% and 57% .